La adaptación de las sociedades cooperativas al nuevo Plan General Contable: análisis de las principales implicaciones económicas y financieras - Martín López, Sonia; Iturrioz del Campo, Javier (REVESCO. Revista de Estudios Cooperativos, 2008)
The Law 16/2007, of reform and adjustment of the mercantile legislation about accounting in Spain, as well as of the General Plan of Accounting, and of the General Plan of Accounting for Small and Medium Companies, they have allowed the incorporation of the new accounting criteria gathered in International Financial Reporting Standards (IFRS) to give response to the aim marked from the European Union of favouring the comparison of the accounting forms elaborated in the different member states, to help to increase this way the transparency of the markets in an economic environment increasingly globally and internationally. Nevertheless, in case of the cooperative societies, the sectorial normative has not been published. This work centres on the analysis of the implications that have in the cooperative societies so much the accounting innovations already published as the aspects that must be fixed in the mentioned sectorial regulation attending to their special characteristics.